Tricks of the trade used to accelerate high-resolution structure determination of membrane proteins. - Sonoda, Y; Cameron, A; Newstead, S; Omote, H; Moriyama, Y; Kasahara, M; Iwata, S; Drew, D (2010)
The rate at which X-ray structures of membrane proteins are solved is on a par with that of soluble proteins in the late 1970s. There are still many obstacles facing the membrane protein structural community. Recently, there have been several technical achievements in the field that have started to dramatically accelerate structural studies. Here, we summarize these so-called 'tricks-of-the-trade' and include case studies of several mammalian transporters.